2019
DOI: 10.32014/2019.2518-170x.14
|View full text |Cite
|
Sign up to set email alerts
|

To the Question of Recovery of Uranium From Raw Materials

Abstract: NAS RK is pleased to announce that News of NAS RK. Series of geology and technical sciences scientific journal has been accepted for indexing in the Emerging Sources Citation Index, a new edition of Web of Science. Content in this index is under consideration by Clarivate Analytics to be accepted in the Science Citation Index Expanded, the Social Sciences Citation Index, and the Arts & Humanities Citation Index. The quality and depth of content Web of Science offers to researchers, authors, publishers, and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…It was revealed that the identified organizational and pedagogical conditions have an impact on the formation of specialists' professionally significant qualities which underlie their productive competitiveness in the field of professional activity (Kenzhaliev B.K et al, 2019;O. B. Kenzhaliyev et al, 2018;Sheriyev et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that the identified organizational and pedagogical conditions have an impact on the formation of specialists' professionally significant qualities which underlie their productive competitiveness in the field of professional activity (Kenzhaliev B.K et al, 2019;O. B. Kenzhaliyev et al, 2018;Sheriyev et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, natural minerals have a low sorption capacity [19,20,21], which can be increased by modification.…”
Section: Main Research Partmentioning
confidence: 99%
“…The states of acceptance and love, empathy and reflection, as well as congruence, authenticity largely arise "automatically": a person comprehends the essence of love and the fact that love is not constant comfort, on the contrary, it implies more or less significant tests, and "Gifts of fate" [18], she is not the end, but all being, she is not permissiveness, but freedom and responsibility, she is the integrity of life, not the division into good and bad, etc. A person and an organization also comprehends that it is easier not to wait for help, but to render it yourself: to the same or even more needy people and groups [11,12,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The purpose of a business is not the maximum profit for the sake of profit, power, etc., but the service of societies, a joint, if possible harmonious, development.…”
mentioning
confidence: 99%